Design and evaluation of a high power density and high energy efficiency fuel element for space nuclear reactors. (5th June 2021) - Deng, Yangbin; Qiu, Bowen; Yin, Yuan; Wu, Yingwei; Su, Guanghui
Highlights: A novel fuel design with dual-cooling was proposed based on TOPAZ-II fuel. Thermionic-thermoelectric models were developed and fuel analysis was conducted. Power density could be increased by 120%, while fuel temperature was decreased. The system conversion efficiency was increased from 9.2% to 13.4%. The system utilization efficiency was increased from 6.6% to 10.2%. Abstract: The enhancement of the power density and efficiency of space nuclear reactors is of great value for space exploitation and exploration. Based on a TOPAZ-II space nuclear reactor, a novel fuel element design was proposed for power density and energy efficiency improvements in this study. In addition to an external thermionic generator in the original fuel design, a heat pipe thermoelectric generator (HPTEG) was implemented on the inside of the fuel ring. This novel design allowed for a significant power density increase while lowering the fuel temperature. Thermionic and thermoelectric simulation models were developed and then implemented in a thermo-mechanical analysis program for a space nuclear fuel element. With this program, the thermo-mechanical, thermionic, and thermoelectric performances during long-term operation were investigated. The results indicated that the maximum allowable power density could be increased by 120% while substantially reducing the fuel temperature in the new design. Compared with a thermionic generator, the HPTEG exhibited the characteristics of high output voltage and low current, which could reduce the joule dissipation and improve the energy utilization efficiency. Due to the high power density, the system energy conversion efficiency was increased from 9.2% to 13.4% and the system energy utilization efficiency was increased from 6.6% to 10.2%.